REcycled meDieval DIplomatic fragmentS Research Project (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
REcycled meDieval DIplomatic fragmentS (REDDIS) is a two-year PRIN 2022 PNRR research project (1 December 2023 – 30 November 2025), funded by the European Union – Next Generation EU, which aims to study the phenomenon of the reuse of manuscript supports bearing documentary texts from the Middle Ages, which have been discarded and transformed to be re-functionalised into objects (books, but not only) that are currently kept in public and private Italian heritage institutions such as archives, libraries, museums, etc.
Keywords: Documents; Middle Age; Discard; Reuse